2016
DOI: 10.1016/j.ynstr.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in subcellular distribution of delta opioid receptors in the rat hippocampus in response to acute and chronic stress

Abstract: Drug addiction requires associative learning processes that critically involve hippocampal circuits, including the opioid system. We recently found that acute and chronic stress, important regulators of addictive processes, affect hippocampal opioid levels and mu opioid receptor trafficking in a sexually dimorphic manner. Here, we examined whether acute and chronic stress similarly alters the levels and trafficking of hippocampal delta opioid receptors (DORs). Immediately after acute immobilization stress (AIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
81
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(101 citation statements)
references
References 93 publications
(170 reference statements)
19
81
1
Order By: Relevance
“…Summary of sex differences in the opioid system following CIS and oxycodone CPP in the rat hippocampus. Our previous light and electron microscopic studies have revealed notable sex differences in mossy fiber LEnk levels and in the redistributions of DORs and MORs in pyramidal cells and GABAergic interneurons following CIS and oxycodone CPP (Mazid et al, ; McEwen & Milner, ; Ryan et al, ). *Females in diestrus; ^Females in estrus…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Summary of sex differences in the opioid system following CIS and oxycodone CPP in the rat hippocampus. Our previous light and electron microscopic studies have revealed notable sex differences in mossy fiber LEnk levels and in the redistributions of DORs and MORs in pyramidal cells and GABAergic interneurons following CIS and oxycodone CPP (Mazid et al, ; McEwen & Milner, ; Ryan et al, ). *Females in diestrus; ^Females in estrus…”
Section: Introductionmentioning
confidence: 98%
“…In males, but not females, CIS downregulates expression of opioid, stress and other signaling molecules in the hippocampus that are important for mediating synaptic plasticity (Randesi et al, ). In mossy fiber‐CA3 synapses, both mossy fiber LEnk levels and DOR density in CA3 dendritic spines remain elevated in females regardless of estrogen state following CIS (Mazid et al, ; Pierce, Kelter, McEwen, Waters, & Milner, ). The increase in DORs in CA3 spines following CIS in females resembles that seen previously in females at high‐estrogen states (Harte‐Hargrove et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence also have suggested that the reinstatement of drug seeking behaviors is mediated by dopamine receptors (Dai, Kang, Wang, & Ma, 2006;Gilbert et al, 2005). As well, Mazid et al, in 2016 suggest that desperate stress could affect opioid-related learning (Mazid et al, 2016). As well, it confirmed that desperate food deprivation facilitate reinstatement of morphine CPP in rats .…”
mentioning
confidence: 87%